Expert views on current and future use of social media among crisis and emergency management organizations: Incentives and barriers - Haataja, Matti; Laajalahti, Anne; Hyvärinen, Jenni (Human Technology, 2016)
Our research explored the use of social media among crisis and emergency management organizations and we present the main incentives and barriers experts perceive in social media adoption by such organizations. The data were gathered via an international online questionnaire sent to crisis communication and management experts. The results indicate that crisis and emergency management organizations use social media specifically to disseminate information to citizens but also increasingly to receive it from citizens. They are motivated to use social media because of the possibility for communicating through them directly, rapidly, and widely, as well as for building responsible relationships and situational awareness. Lack of knowledge, time, and role models for implementation, as well as inflexible and old-fashioned organizational culture, were the main barriers mentioned for not utilizing social media. Based on the results, further effort should be put into promoting the dissemination of knowledge, best practices, and experiences of using social media across the various actors and organizations providing crisis response.